Anthropometric Parameters in Celiac Disease: A Review on the Different Evaluation Methods and Disease Effects - Allysson Costa; Gleisson A. P. Brito (Journal of Nutrition and Metabolism)
This review compiled anthropometric data from 29 original articles, published between 1995 and 2015, corresponding to a total sample of 6368 celiac disease subjects. Body mass index was the main parameter for measuring anthropometry (82.1%), followed by body mass (78.6%), body fat (51.7%), bone mineral density and bone mineral content (46.4%), and fat-free mass (44.8%). The main evaluation method was dual x-ray absorptiometry (83.3%), followed by bioimpedance (16.6%), skinfold thickness (16.6%), and isotope dilution (5.5%). This compilation suggests that celiac disease patients without a gluten-free diet (WGFD) and celiac disease patients with a gluten-free diet (GFD) show a lower body mass than the control group, with inconclusive data about WGFD versus GFD. Body mass index is lower in WGFD and GFD compared to control group, and is lower in WGFD compared to GFD. We observed lower values of FM and FFM in WGFD and GFD versus the control group. No difference was found between WGFD versus GFD. BMD and BMC are lower in WGFD versus GFD and GFD versus the control group, with inconclusive data about WGFD versus GFD. The findings of this review suggest that celiac disease patients must be periodically evaluated through anthropometric parameters, since the pathology has the potential to modulate such values even in a gluten-free diet, with these variables reflecting their healthy status. In parallel, the screening of different anthropometric assessment methodologies can provide support for more accurate evaluations by scientists and clinical professionals who work with celiac disease patients.